2020
DOI: 10.3390/polym12112729
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane/Nanosilver-Doped Halloysite Nanocomposites: Thermal, Mechanical Properties, and Antibacterial Properties

Abstract: In this study, the researchers successfully embellished the surface of halloysite (Ag/HNTs) with silver using halloysite, silver nitrate (AgNO3), and polyvinylpyrrolidone (PVP). The researchers then prepared polyurethane that contained pyridine ring by using 4,4′-diphenylmethane diisocyanate (MDI) and polytetramethylene glycol (PTMG) as the hard chain segment and the soft chain segment of polyurethane (PU), as well as 2,6-pyridinedimethanol (2,6-PDM) as the chain extension agent. This was followed by the prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The results revealed the water contact angles of PVDF-TrFE, CNT-COOH/PVDF-T 1 wt%, and CNT-COOH:SMA EF40-M/PVDF-T 1:1 were 80.9, 100.9, and 107.2 • . The results indicated that the contact angle to water has a significant upward trend when CNT-COOH was added to PVDF-TrFE because the carbon nanomaterials are distributed on the surface of PVDF-TrFE when PVDF-TrFE was added with CNT-COOH, thereby increasing the surface roughness, which has been reported in previous studies [32,33]. Subsequently, it can be found that the water contact angle increased from 100.9 to 107.2 • by adding SMA EF40-M, which may be because SMA EF40-M can improve CNT-COOH dispersal in PVDF-TrFE.…”
Section: Dispersion Stability Of Cnt-cooh Using Polymeric Dispersantsupporting
confidence: 65%
“…The results revealed the water contact angles of PVDF-TrFE, CNT-COOH/PVDF-T 1 wt%, and CNT-COOH:SMA EF40-M/PVDF-T 1:1 were 80.9, 100.9, and 107.2 • . The results indicated that the contact angle to water has a significant upward trend when CNT-COOH was added to PVDF-TrFE because the carbon nanomaterials are distributed on the surface of PVDF-TrFE when PVDF-TrFE was added with CNT-COOH, thereby increasing the surface roughness, which has been reported in previous studies [32,33]. Subsequently, it can be found that the water contact angle increased from 100.9 to 107.2 • by adding SMA EF40-M, which may be because SMA EF40-M can improve CNT-COOH dispersal in PVDF-TrFE.…”
Section: Dispersion Stability Of Cnt-cooh Using Polymeric Dispersantsupporting
confidence: 65%
“…In order to solve these problems, it has been reported that mineral powders including nano clay and nano silica are used as UF fillers in scientific research [ 32 , 33 , 34 , 35 , 36 ]. These fillers can prevent the excessive penetration of resin into wood pores, improve the initial viscosity, reduce the internal stress of cured adhesive layer, improve the aging resistance of glued wood-based panels, and reduce the formaldehyde emission [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that pullulan (PL) exists in an amorphous state [ 40 ]. The incorporation of Ag-NPs and irradiation techniques was previously shown to transform the solution to exhibit crystallization characteristics [ 41 ]. Four (4) diffraction peaks can confirm the purity of the silver formation at 2θ of 38.54°, 44.91°, 65.04°, and 78.11°, corresponding to the (111), (200), (220), and (311) planes of the face-centered cubic (FCC) structure [ 42 ].…”
Section: Resultsmentioning
confidence: 99%